Late Holocene sedimentation in a high Arctic coastal setting: Simpson Lagoon and Colville Delta, Alaska - Hanna, Andrea J. M.; Allison, Mead A.; Bianchi, Thomas S.; Marcantonio, Franco; Goff, John A. (Continental Shelf Research, 2014)
Arctic coastal environments near major river outfalls, like Simpson Lagoon, Alaska and the adjacent Colville River Delta, potentially contain high-resolution sediment records useful in elucidating late Holocene Arctic sediment transport pathways and coupled terrestrial-ocean evidence of paleoclimate variability. This study utilizes a multi-tracer geochronology approach (137Cs, 239,240Pu, and 14C) tailored for high-latitude environments to determine the age models for cores collected from Simpson Lagoon, and to date seismic boundaries in shallow acoustic reflection data (CHIRP) to examine late Holocene infill patterns. Modern (~100 y) sediment accumulation rates range from 5 m of late Holocene interbedded sediments, likely derived primarily from the Colville River, with onset of accumulation occurring prior to ~3500 y BP. A paleo-high in central Simpson Lagoon, separating the two depocenters, was subaerially exposed prior to ~600 y BP. The millimeters-per-year sedimentation rates across the lagoon, coupled with the undisturbed, interbedded sediment record, indicate that these settings hold great potential to develop new Arctic paleoenvironmental records.